Clinical profile and outcome of diphtheria in central India: a retrospective observational study - Meshram, Rajkumar M.; Patil, Ashwini (International Journal of Contemporary Pediatrics, 2018)
Background: Although, diphtheria is eliminated by many developed countries by effective immunization, still diphtheria continues to be endemic in India and leading cause of morbidity and mortality, especially in areas in the border of the two states. The objective of the present study was to recognize the clinical profile, morbidity and mortality pattern of diphtheria and to study their immunization status as a retrospective observational study performed in pediatric wards and paediatric intensive care unit. Methods: The medical records were recovered from the case files, searching for cases diagnosed as diphtheria from the Medical Record Section and Statistical Service of the institute. A pre-established protocol was formed after approval from institutional ethical committee. Case study included suspected, probable and confirmed cases of diphtheria as per the WHO definition guidelines. All the relevant data and information regarding age, gender, residence, socioeconomic status, immunization status, clinical details, laboratory investigation, complications, and treatment provided, and outcome were recorded. Results: Amongst 47 patients, 55.32% were >5years and mean age was 6.46±3.08 years with no difference in sex distribution. 2(4.25%) patients were completely immunized, 27(57.45%) were partially immunized and 18(38.30%) were not immunized. An immunization rate was less in females as compared to males. All patients presented with fever and membrane in throat followed by throat pain 95.74%, enlarged/congested tonsils 80.85%, respiratory difficulty 68.08%, dysphagia 59.57% bull neck 48.94% and voice change 36.17%. Myocarditis was the commonest (42.55%) complication followed by palatal palsy (14.89%), polyneuropathy (8.51%), acute renal failure (4.25%) and DIC & shock (4.25%) were observed. Case fatality rate was 21.28%. Maximum numbers of cases were noted during the rainy season. Conclusions: Shifting of occurrence of diphtheria in the age group of 5-15 years suggest the need to improve and strengthen the immunization activity specially booster doses in the border districts as most of the cases were from areas at the border of two states.